A dual-function battery for desalination and energy storage. Issue 10 (3rd September 2018) - Wang, Liubin; Mu, Chaonan; Li, Haixia; Li, Fujun
Abstract : A dual-function battery composed of a NaTi2 (PO4 )3 anode and a Ag cathode with NaCl aqueous electrolyte has been reported for simultaneous seawater desalination and renewable energy storage. Abstract : Desalination of seawater and renewable energy storage are quite promising for a sustainable society, but their combination for high efficiency is a difficult task. Herein, we demonstrate a dual-function battery, which is composed of a NaTi2 (PO4 )3 anode and a Ag cathode with NaCl aqueous electrolyte, for desalination and electrical energy storage. In a charging process, Na + and Cl − are extracted from the electrolyte and inserted into the separate electrodes, while in a reverse process, the stored electricity and ions are released into electrolyte. As a demonstration, the dual-function battery can be continuously photocharged with a solar cell and discharged for 50 cycles without significant decrease in both the discharge voltage and capacity. This study will provide new insights into both seawater desalination and efficient renewable energy utilization.